Innovación: ¿De dónde proviene realmente la creatividad? - Arroyo Andonaire, Gerardo Enrique (2017)
Organizations around the world are looking to be more competitive the last years, in that way, organizations demand workers with innovative and creativity skills. So now exist many tools for generating innovative ideas and impact in the organizations and its necessities. The most wellknown methodologies are Design Thinking and Lean Startup. Nevertheless, many researchers and specialists mentioned that these methodologies are not enough to generate innovative solutions because the real creativity was killed by the education system. Also, universities and organizations do not help on that. There is evidence that affirms a creative power in each person and that potential we can rediscover. Based on that organizations can generate innovative solutions.